Hubungan Karakteristik Bank dengan Harga Saham - H. Mas'ud, Muchlis; Anggarani, Dwi; Zulkifli (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
This study discusses the influence of variable bank characteristics on bank stock prices included on the Indonesia Stock Exchange (2009-2013). Regarding what is used is a data collection that is a merger between cross section data and time series from 25 banks. The results showed that bad credit as a proxy for credit risk increased significantly to stock prices. Credit risk increases. It is proven that efficiency shows a negative and significant relationship to stock prices. Limitations / Implications in this study are the adequacy of bank capital, profitability and income diversification ratio non-interest income (NIIR) does not affect the bank's stock price.